The Expansionist Politics of Sultan Agung and Turning Away the Sea in the 17th Century: Rereading Javanese Historiography - Miftahuddin; Ajat Sudrajat; Danar Widiyanta; Ita Mutiara Dewi; Kuncoro Hadi; Raymizard Alifian Firmansyah (istory Department, Faculty of Social Sciences, Universitas Negeri Semarang in collaboration with Masyarakat Sejarawan Indonesia (Indonesian Historical Society), 2025)
Abstract: This article develops a thesis by Adrian B. Lapian and contextualizes the Islamic rule in Java that stimulated the movement of the sea people to turn their backs on the sea. It critiques conventional historiography that focuses only on heroic stories. Using critical maritime history studies, this article presents a re-reading of the political narrative of Sultan Agung's expansion into North and East Java. The history of Java is not only about political power and conflicts between Javanese kingdoms in the 17th century, but also about expansion, social problems, socio-political domination, and the erasure of collective memory of maritime culture. Therefore, this research attempts to write history with an alternative perspective to examine the